2013
DOI: 10.1039/c3ta12538f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine microporous and mesoporous activated carbon fibers from alkali lignin

Abstract: A facile and sustainable approach has been successfully devised to fabricate ultrafine (100-500 nm) highly porous activated carbon fibers (ACFs) by electrospinning of aqueous solutions of predominantly alkali lignin (low sulfonate content) followed by simultaneous carbonization and activation at 850 C under N 2 . Incorporating a polyethylene oxide (PEO) carrier with only up to one ninth of lignin not only enabled efficient electrospinning into fibers but also retained fibrous structures during heating, allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 43 publications
1
100
1
Order By: Relevance
“…The two stage mass losses corresponded to two major exotherms at 310 and 455°C, indicative of the respective hemicelluloses and lignin decomposition. Assuming complete decomposition of hemicelluloses into volatiles and 60% alkali lignin char at 600°C, 43 HL was estimated to contain 65% hemicelluloses and 35% lignin, similar to their proportion in raw rice straw.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two stage mass losses corresponded to two major exotherms at 310 and 455°C, indicative of the respective hemicelluloses and lignin decomposition. Assuming complete decomposition of hemicelluloses into volatiles and 60% alkali lignin char at 600°C, 43 HL was estimated to contain 65% hemicelluloses and 35% lignin, similar to their proportion in raw rice straw.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These lignin peaks resembled those derived from softwood via commercial alkali pulping process. 43 The EDX elemental analysis of HL showed 61.5% C and 38.5% O in mass (Figure 2b) with C content in between that of lignin (58 to 65%) 44−46 and hemicelluloses (38 to 42%). 44,47 ACNF consisted of 47.2% C, 50.6% O and 2.2% Na in mass, with a 1.24 C/O atomic ratio very close to the 1.2 C/O ratio of pure cellulose.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The ultrafine ACFs were electrospun from lignin and simultaneously carbonized and activated at 900°C to high specific surface (1400 m 2 /g) and pore volume (0.7 cm 3 /g). 31 The solid acid catalysts from ligninbased ACFs have several advantages and desired attributes over other solid acid catalysts for hydrolysis of crystalline cellulose. Lignin, an abundant and underutilized biomass fraction, is an excellent carbon precursor, and lignin chars are less recalcitrant than rigid graphitic carbons, such as carbon nanotubes, 18 to be readily sulfonated by concentrated sulfuric acid, a much safer alternative than the commonly used fuming sulfuric acid for sulfonation of graphitic carbons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both carbon fibers (CFs) and activated carbon fibers (ACFs) were synthesized according to a previously reported approach. 31 Briefly, aqueous 9:1 w/w AL ls /PEO (10 wt % total concentration) mixtures without and with NaOH at a 1:2 w/w NaOH/lignin ratio were electrospun into CF and ACF precursor fibers, respectively. The precursor fibers were placed in a quartz tube (2 cm inner diameter) of an electric furnace (Mini-Mite, Lindberg/Blue), heated at 10°C min −1 under flowing N 2 at 100 mL min −1 to 105°C, held for 0.5 h to drive off moisture, and then to 600 (CFs) or 900°C (CFs and ACFs), held for another 0.5 h, and finally cooled to ambient temperature under flowing N 2 at 100 mL min −1 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some authors studied the electrospinning of n-fractionated SKL solutions together with various concentrations of suspended MWCNTs (Lin et al, 2013;Teng et al, 2013). Furthermore, it has been reported that the presence of 10 wt% PEO enables the efficient electrospinning of aqueous NaOH or KOH/Alcali-lignin (AL ls ) solutions into fibers (Hu and Hsieh, 2013;Hu et al, 2014). Another outstanding method to assist the spinning of advanced fine lignin fibers is the emulsion electrospinning (Lin et al, 2013).…”
Section: Electrospinningmentioning
confidence: 99%